The reduced distribution functions for charged particles with many-body interactions - Kahlbaum, T. (Condensed Matter Physics, 2001)
We consider a multi-component system of charged particles that interact
via a general many-body potential, and calculate the reduced distribution
functions from the Bogoliubov-Born-Green-Kirkwood-Yvon hierarchy
of equations in the form of a screened virial expansion through second
order Ми розглядаємо багатокомпонентну систему заряджених частинок,
які взаємодіють через загальний багаточастинковий потенціал, і обчислюємо функції розподілу з ієрархії рівнянь Боголюбова-Борна-Ґріна-Кірквуда-Івона у формі екранованого віріального розкладу до
другого порядку включно.